(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
With his psychoanalytic theory, Sigmund Freud asserts that human behavior mostly occurs in the subconscious part of the brain. This theory leaves many questions for those interested in studying human behavior, as it leaves many questions for them. One of the most important of these questions is can a person really control his behavior? Freud’s theory of the unconscious divides it into three drives: the id, the ego, and the superego. Ed is the most aggressive behavior in humans. The super ego is the part responsible for the moral aspect that pushes a person to do well. As for the ego, it is that part of the dengue that strives to find a middle ground between the id and the superego. Thus, the current study aims to identify the cause of corruption of human soul through analyzing the British novelist Cormac McCarthy’s The Road. It will illustrate the human struggle for survival under a circumstance in which the law collapses and the ethics that are the basis of human interaction for the permanence of life disappear. It also sheds light on how to solve this problem. It should be noted that the study is formatted in APA (8) writing style in discussing the study and documenting the primary and secondary resources.